(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2022)
Le fondazioni greche di Magna Grecia e di Sicilia in rapporto con gli insediamenti indigeni preesistenti. Si discutono i modelli mentali ellenici, ricavati dalle fonti letterarie, relativi alle forme delle fondazioni in Occidente. Si ritiene che tali fondazioni siano state operazioni condotte dalle poleis e non da privati. Si confrontano le strutture, archeologicamente note, delle fondazioni greche occidentali con quelle degli insediamenti indigeni. La mancanza di condizionamenti territoriali e cultuali, insieme alla impostata regolarità dei lotti agricoli, ha condotto a forme urbanistiche che, dalle poleis occidentali sono state imitate in Grecia propria. The Greek foundations of Magna Graecia and Sicily are discussed in relation to the pre-existing indigenous settlements: the Hellenic mental models, as drawn from literary sources, in relation to the forms of foundations in the West. Evidence indicates that these foundations were operations conducted by the poleis and not by private individuals. The archaeologically known structures of western Greek foundations are compared with those of the indigenous settlements. The lack of territorial and religious conditions, together with the set regularity of agricultural lots, led to urban planning forms that derived from the western poleis and were imitated on the Greek mainland.